Management of Suspected Cases of Feline Immunodeficiency Virus Infection in Eurasian Lynx (Lynx lynx) During an International Translocation Program - Ryser-Degiorgis, Marie-Pierre; Marti, Iris; Pisano, Simone R. R.; Pewsner, Mirjam; Wehrle, Martin; Breitenmoser-Würsten, Christine; Origgi, Francesco C.; Kübber-Heiss, Anna; Knauer, Felix; Posautz, Annika; Eberspächer-Schweda, Matthias; Huder, Jon B.; et al. (Frontiers in Veterinary Science, 2021)
The Eurasian lynx (Lynx lynx) population in Switzerland serves as a source for reintroductions in neighboring countries. In 2016-2017, three lynx from the same geographical area were found seropositive for Feline Immunodeficiency Virus (FIV) in the framework of an international translocation program. This novel finding raised questions about the virus origin and pathogenicity to lynx, the emerging character of the infection, and the interpretation of serological results in other lynx caught for translocation. Archived serum samples from 84 lynx captured in 2001-2016 were retrospectively tested for FIV antibodies by Western blot. All archived samples were FIV-negative. The three seropositive lynx were monitored in quarantine enclosures prior to euthanasia and necropsy. They showed disease signs, pathological findings and occurrence of co-infections reminding of those described in FIV-infected domestic cats. All attempts to isolate and characterize the virus failed but serological data and spatiotemporal proximity of the cases suggested emergence of a lentivirus with antigenic and pathogenic similarities to FIV in the Swiss lynx population. A decision scheme was developed to minimize potential health risks posed by FIV infection, both in the recipient and source lynx populations, considering conservation goals, animal welfare and the limited action range resulting from local human conflicts. Development and implementation of a cautious decision scheme was particularly challenging because FIV pathogenic potential in lynx was unclear, negative FIV serological results obtained within the first weeks after infection are unpredictable, and neither euthanasia nor repatriation of multiple lynx were acceptable options. The proposed scheme distinguished between three scenarios: release at the capture site, translocation, or euthanasia. Until April 2021, none of the 40 lynx newly captured in Switzerland tested FIV-seropositive. Altogether, seropositivity to FIV was documented in none of 124 lynx tested at their first capture, but three of them seroconverted in 2016-2017. Diagnosis of FIV infection in the three seropositive lynx remains uncertain but clinical observations and pathological findings confirmed that euthanasia was appropriate. Our experiences underline the necessity to include FIV in pathogen screenings of free-ranging European wild felids, the importance of lynx health monitoring, and the usefulness of health protocols in wildlife translocation.